Post-compression of the GW-level femtosecond pulse in a solid-state multi-pass cell - Liya Shen; Jiajun Song; Yujie Peng; Guangxin Luo; Yinfei Liu; Jianyu Sun; Yuxin Leng (High Power Laser Science and Engineering)
We demonstrate the post-compression of the GW-level femtosecond pulse in a solid-state multi-pass cell (MPC) by the pre-chirp management method. When the laser pulse is positively pre-chirped, the 200 μJ 170 fs input pulse is compressed to 163 μJ 44 fs at the output, corresponding to a transmission of 81% and a pulse shortening factor of 3.86. When the laser pulse is negatively pre-chirped, the spectral evolution, as the pulse propagates in the MPC, is characterized and, eventually, the pulse duration is compressed to 51 fs, corresponding to a pulse shortening factor of 3.3. After the driving laser goes through the pre-chirp managed MPC device, the power stability and beam quality are almost preserved. The experimental results offer a viable path toward the post-compression of high-peak-power laser pulses.